Proyecto de Factibilidad para la creación de una empresa Productora y Comercializadora de helados de frutas y verduras, en la Ciudad de Catamayo - Valarezo Valarezo, Sonia Patricia (2016)
This work, research was conducted with the purpose of making a 'PROJECT FEASIBILITY FOR THE CREATION OF A COMPANY PRODUCER AND DISTRIBUTOR FOR ICE CREAM OF FRUITS AND VEGETABLES IN THE CITY OF CATAMAYO "seeks to offer a quality product with a high nutritional value, at low cost and equally take advantage of business opportunities and business development within the market, which have not yet been explored. The study is based on a literature review for the compilation of information the survey technique applied to consumers by families in the city of Catamayo, as well as producers of ice cream, respectively, of which information concerning was collected to existing demand. Among the results of the market study, which was conducted through surveys of both plaintiffs and bidders, it allowed an analysis of supply and demand, therefore it was determined that for the first year there is an effective demand for 77 % of frozen fruits and vegetables and an offer of 20,635.00 in this way is obtained that unmet demand is 658.518,00 frozen fruits and vegetables for the first year. The technical study where the size of the plant in relation presents installed capacity of the company for the production of frozen fruits and vegetables and capacity utilization is then developed, defined its macro and micro location. The company will be located in the city of Catamayo, in the Canoas neighborhood, 6 considered commercial hub, is a strategic and accessible sector to enable citizens to acquire the product. In the organizational study found that the company will be legally incorporated as a Limited Company, just as organic, functional and positional structure and the proposed manual functions are established, will have a period of a minimum duration of 5 years and will as reason social "World D" Sabores "Cia. Ltda. The economic and financial study gave learn about the project investment dollars is $ 12,377.61, the same that will be financed 60% by the partner and 40% with credit Fomentos National Bank, with an interest rate of 11% annually. The unit production cost for the first year will be $ 0.23 cents, increasing a profit margin of 20%, resulting in a retail price of $ 0.27, earning sales revenue of $ 79.422,76. dollars for the first year. The evaluation of the project to establish the suitability of the project and its implementation for which the following indicators such as net (NPV) Present value analyzed the same that is $ 71.529,38 if the project is accepted as greater investment initial; Internal Rate of Return (IRR) is 137,57 the project is accepted, Benefit Cost Ratio is 1.29 which means that for every dollar invested in the project, utility generates $ 0.29 in the company; Recovery Period Capital (PRC) is 1 one,y 6 months and, finally sensitivity analysis with increased costs is the 15,00 % shows that the project is not sensitive; sensitivity analysis in revenue decline of 12,00 % is the same as favorable indicate that the implementation of the project. 7 Finally, conclusions and recommendations reached at the end of work are presented, accompanied by the bibliography consulted with their respective annexes.